Self-medication practices during the COVID-19 pandemic among the adult population in Peru: A cross-sectional survey - Quispe-Cañari, Jean Franco (2021)
Self-medication impacts both negatively and positively the health of people, which has become evident during the COVID-19 pandemic. The study aimed to assess the prevalence of self-medicated drugs used for respiratory symptoms, as COVID-19 preventive, for its symptoms or once tested positive. To determine the perception of symptom relief and demographic variables that promote self-medication in Peru. We performed a cross-sectional, analytical, multicenter study in 3792 study respondents on the use, the reason for use, and perception of relief after the use of six drugs during the quarantine period. An online questionnaire was developed, pretested and submitted to the general public. Multivariable logistic regression was used to ascertain factors that influence an individual’s desire to self-medicate, associations were considered significant at p < 0.05 and using region (coast, mountain and jungle) as cluster group. The majority of respondents self-medicated with acetaminophen for respiratory symptoms and mainly because they had a cold or flu. It was observed that all the surveyed drugs (acetaminophen, ibuprofen, azithromycin, penicillin, antiretrovirals and hydroxychloroquine) were consumed for various symptoms including: fever, fatigue, cough, sneezing, muscle pain, nasal congestion, sore throat, headache and breathing difficulty. Over 90% of respondents perceived relief of at least one symptom. Multivariable logistic regression showed that older people have a higher frequency of antiretroviral self-medication, respondents who currently have a job had a higher frequency of penicillin self-medication, and that respondents from the Andes consumed less acetaminophen, while the ones from the rainforest consumed it more. There were significant percentages of self-medication, including drugs without sufficient scientific evidence. Age, region where one lived and job status were variables associated with self-medication frequency. Continuous awareness and sensitization about the risks of self-medication are warranted.